Online Identification Using RLS Algorithm and Kaczmarz’s Projection Algorithm for a Bioreactor Process (International Journal of Engineering and Computer Science, 2014)
The control theory and automation technology is widely used in industries. Many control algorithms are based on the mathematical models of dynamic systems. Mathematical models and parameter estimation are basics for automatic control. A recursive least squares parameter estimation algorithms and Kaczmarz’s projection algorithm is applied based on ARMAX model and OE models. The estimated parameters are compared with the true ones. The proposed method has been applied to identify the parameters of bioreactor process